Outcomes and surgical tips in the management of accessory parotid lobe tumours - Rabindra P. Singh; Ausama Alaani; Richard Oakley; Jean-Pierre Jeannon; Ricard Simo (Elsevier, 2021)
The tumours of the parotid accessory lobe may present with significant challenges to the clinicians due to their rarity, presenting with diagnostic difficulties as well as difficult decision-making in terms of surgical approach.We retrospectively analysed 8 cases of accessory parotid lobe tumours treated in our unit. The presenting symptom was a mass in all cases present in the peri-parotid region with duration ranging from 6 weeks to 2 years. All cases were investigated with ultrasound-guided fine needle aspiration cytology (FNAC). Various surgical approaches were adopted that included standard cervico-facial (n = 4), trans-oral (n = 3) and cervical (n = 1) incision approach. The rate of early post-operative facial nerve weakness was 37.5% (n = 3). There were no cases of tumour recurrence.Any lump not typical of a parotid lump but close to the parotid region should be treated with a high degree of suspicion to exclude an accessory lobe tumour. A full work up with US-guided FNAC is recommended prior to definitive treatment. Although a standard cervico-facial incision approach is recommended in most cases, other direct approaches may also be considered depending on the location of the tumour. We present our experience of these tumours providing practical tips on diagnosis and surgical management.